2016
DOI: 10.1016/s1470-2045(16)30148-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk of extranodal natural killer T-cell lymphoma: a genome-wide association study

Abstract: Top-Notch Young Talents Program of China, Special Support Program of Guangdong, Specialized Research Fund for the Doctoral Program of Higher Education (20110171120099), Program for New Century Excellent Talents in University (NCET-11-0529), National Medical Research Council of Singapore (TCR12DEC005), Tanoto Foundation Professorship in Medical Oncology, New Century Foundation Limited, Ling Foundation, Singapore National Cancer Centre Research Fund, and the US National Institutes of Health (1R01AR062886, 5U01GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 57 publications
4
59
0
3
Order By: Relevance
“…Among the sporadic NKTLs with available tissue for IHC ( n  = 14), two displayed weak-cytoplasmic staining for FAM160A1, while the rest were negative. Examination of mutation frequencies in sporadic NKTL cases, derived from Singapore ( n  = 33) and Chinese cohorts ( n  = 189) in a previously published dataset 3 , did not reveal any FAM160A1 c.2827C > T variants. Furthermore, a preliminary analysis of our in-house clinical dataset of sporadic NKTL suggests that higher expression of FAM160A1 did not lead to differences in survival outcomes (data not shown).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Among the sporadic NKTLs with available tissue for IHC ( n  = 14), two displayed weak-cytoplasmic staining for FAM160A1, while the rest were negative. Examination of mutation frequencies in sporadic NKTL cases, derived from Singapore ( n  = 33) and Chinese cohorts ( n  = 189) in a previously published dataset 3 , did not reveal any FAM160A1 c.2827C > T variants. Furthermore, a preliminary analysis of our in-house clinical dataset of sporadic NKTL suggests that higher expression of FAM160A1 did not lead to differences in survival outcomes (data not shown).…”
Section: Introductionmentioning
confidence: 79%
“…Recently, some progress has been made in uncovering the molecular pathogenesis of NKTL. In a genome-wide association study, strong correlations between HLA-DPB1 single-nucleotide polymorphisms and NKTL susceptibility were discovered, implicating altered antigen processing and presentation to CD4-positive T-lymphocytes in this Epstein-Barr virus (EBV)-associated malignancy 3 . Next generation sequencing also revealed recurrent somatic mutations such as TP53 , JAK3 , STAT3 and DDX3X in NKTL 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…CD30 has numerous biological functions, including cell cycle arrest, apoptosis, and activation of the prosurvival transcription factor of activated B cells. It is preferentially expressed in activated B cells but is also expressed in T cells and NK cells . .…”
Section: Discussionmentioning
confidence: 99%
“…A recent genome-wide association study (GWAS) [24] showed that “oropharyngeal cancer associations were limited to the human leukocyte antigen (HLA) region, and this association was considerably stronger in HPV-positive cancers.” What is more intriguing is that HLA again appears to play an important and consistent role in several other virus-related cancers, such as NPC [25], extra-nodal natural killer T-cell lymphoma [26], EBV-positive Hodgkin’s lymphoma [27], and chronic hepatitis B-associated hepatocellular carcinoma [28]. …”
Section: Hpv-positive Opcmentioning
confidence: 99%